Determination of seroprevalence of leptospirosis in cattle in Elazig - Çetinkaya, B; Ertas, HB; Muz, A; Öngör, H; Kalender, H; Özdemir, V (Scientific Technical Research Council Turkey, 1999)
Serum samples collected from randomly-selected 395 cattle between June-November 1997 from the districts and central villages of Elazig were used to determine the seroprevalence of Leptospirosis in cattle. Microscopic Agglutination Test (MAT) was used to examine serum samples for antibodies to L. hardjo, L. grippotyphosa, L. pomona and L. icterohaemorrhagiae. Positive results were obtained from eight (2.03%) samples; seven (1.77%) of which were agglutinated with L. hardjo and one (0.25%) with L. grippotyphosa antigens. There was a statistically significant difference when the seropositivity rates were compared in different districts (p=0.002). Age and sex were not determined to affect the frequency of Leptospirosis significantly (p>0.05). According to these results, the seroprevalence of Leptospirosis in cattle was lower in this region when compared to other parts of the country. In addition, L. hardjo was the commonest serovar in this region.
Keywords: Leptospirosis; cattle; microscopic agglutination test